Punishment for rape in Islamic law. - Mohd Noor, Azman (LexisNexis, 2009)
In Islam, rape is considered to be a serious sexual crime. Since it consists of forcible sexual intercourse, most of the classical jurists called it zina bi al-ikrah, that is, forcible unlawful sexual intercourse. The questionarises as to whether rape is part of zina or an isolated crime. This paper focuses on the notion of rape, including a definition of this crime, its punishments and a comparison between rape and zina in Islamic jurisprudence